The Decline of the US Cucumber and Squash Industry - Feng Wu; Zhengfei Guan; Kuan-Ming Huang (EDIS)
The US production of cucumbers and squash has been declining over the last two decades while imports have grown significantly. In particular, imports from Mexico have surpassed US domestic production and have become a major source of cucumber and squash supply in the US market. This publication provides a comprehensive overview of cucumber and squash production and trade to help policymakers, business communities, and researchers understand the structural changes in the market.